Evaluación del nivel de presión sonora en el terminal terrestre de Rocafuerte - Burgos Cadena, Cristhian Leonardo (2023)
Excess noise is a global problem with a high frequency in transportation terminals, where the maximum levels established by the respective regulations of the country where it originates are generally exceeded. The purpose of this work is to evaluate the sound pressure levels in the land terminal in Rocafuerte city, taking as a reference the provisions of the Unified Text of Environmental Legislation (TULSMA) for the evaluation and management of noise. The sound pressure level was evaluated at different points of the terminal through the application of five monitoring points located 50 meters apart; a noise map was drawn up and corrective and preventive measures were proposed. The sound pressure level was above the maximum limit established by the TULSMA (60 dB), with a range of 66 to 82 dB, being the point located in the center of the terminal the one that obtained the highest noise, in addition, the midday period obtained higher levels with 70.3 to 82.6 dB. The measures were mainly focused on reducing the noise generated in the environment, reducing the noise from the emission source, and making proposals to the authorities in charge of the terminal.